Assessment of the factors and impact of obese sedentary employee membership in the composite structured exercise program - Godefroid Kusuayi Mabele; Constant Nkiama Ekisawa; Christophe Delecluse; François Lepira Bompeka; Aliocha Nkodila Natuhoyila; Betty Miangindula; Pierre Akilimali (Turkish Journal of Kinesiology, 2019)
The objective is to determine the factors influencing and the impact of obese worker membership in the structured mixed exercise program. Analytical cross-sectional study of 157 obese workers, aged 18 to 59, randomly selected and subjected to a 3-day, one-day, moderate-intensity, structured exercise program of moderate-intensity to high including jogging, aerobic gymnastics, basketball, volleyball, swimming, abdominals, and walk of 10,000 not at the rate of three working days and two days of weekend recorded using a pedometer. This program has been combined with low-calorie nutrition education, rich in fiber and vitamins and have been associated with spontaneous physical exercise. The factors influencing the adherence of obese workers to the mixed structured exercise program were measured by the positive personal motivation associated with membership. Motivation to undertake the intervention program resulted from the home exercise program, attendance at appointments, better follow-up of prescribed protocols, and better self-reported adherence. Logistic regression was used to identify independent determinants of adherence to the intervention program. The value of p <0.05 defined the threshold of statistical significance. The overall adherence rate of obese workers to the exercise program was 84.1%. Cardiovascular risk factors were significantly higher in the more adherent compared to the less adherent (p = 0.001). Obesity, age under 50, and females were the major determinants of joining the structured mixed exercise program and multiplied by 5 if employees were obese and older. Less than 50 years (OR aj = 4.91 95% CI (1.36-6.14), p = 0.001 for the obese and OR aj = 4.87 95% CI (1.53-6.48), p = 0,000 for age under 50), and 2 for obese women (OR aj = 2.06 95% CI (1.23-4.79), p = 0.000). Obesity, female gender, and age under 50 influence and increase obese adherence to the mixed structured exercise program. The latter positively improve the associated cardiovascular, metabolic and behavioral risks in the context of occupational health.